PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI SELEKSI PENERIMAAN MAHASISWA BARU MENGGUNAKAN SPK - Slamet Rahayu (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Politeknik Negeri Subang is one of the universities with a registration system for new student candidates through an independent examination path which is still offline and a decision support system that is taken based on the results of the decision of the meeting from the committee of the admission of new students, department and deputy. From the existing problems, the author tries to build a new student admission selection information system using a decision support system at the Subang State Polytechnic using the PHP programming language, and XAMPP as a web server, MySql as the database so that the process of input and data processing is faster, as well as profile matching method as a method used in decision support systems. With this system, it is hoped that it can help the Subang State Polytechnic in the new student admission selection process using a decision support system.Keywords: New Student Admission, Profile Matching Method, SPK.